Packaging materials for power storage devices
By using a multi-layered film-like material in the packaging material of lithium-ion batteries, the problem of poor bonding of the protective film residual adhesive and PSA tape is solved, and the excellent appearance and performance of the packaging material are achieved.
Patent Information
- Application Number
- CN202080031772.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-05-15
- Filing Date
- 2020-04-28
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2040-04-28
AI Technical Summary
The prior art is difficult to ensure that the lightly adhesive protective film has no residual adhesive when manufacturing lithium-ion batteries, and that the strongly adhesive PSA tape is firmly bonded to the outer surface of the packaging material.
A film-like encapsulation material with a multi-layer structure includes a substrate protective layer, a substrate layer, an adhesive layer, a metal foil layer and a sealant layer. The substrate protective layer is composed of a curable resin mixed with a variety of particles of different average particle sizes, and a polyol is used as the main agent and a polyisocyanate as the curing agent. By adjusting the average particle size and mixing amount of large and small fillers, the protective film is easily peeled off and the PSA tape is firmly bonded.
The protective film is peeled off without residual adhesive and firmly bonded to the PSA tape, ensuring the excellent appearance and performance of the packaging material.
Smart Images

Figure CN113785374B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a packaging material for an electricity storage device. Background Art
[0002] As a power storage device, for example, secondary batteries such as lithium ion batteries, nickel-metal hydride batteries, and lead storage batteries, and electrochemical capacitors such as double-layer capacitors are known. Due to the miniaturization of portable devices or the limitation of installation space, the power storage device is required to be further miniaturized, and lithium ion batteries with high energy density have attracted much attention. As a packaging material for lithium ion batteries, metal cans were used in the past, but gradually, film-shaped packaging materials that are lightweight, have high heat dissipation, and can be produced at low cost are used.
[0003] The film-like packaging material plays a role in preventing moisture from penetrating into the interior of the lithium-ion battery. Therefore, as the film-like packaging material, a film having a multilayer structure including a metal foil in the layer structure can be used. Then, the film-like packaging material is cold-formed to form a recess, in which the battery contents are accommodated, and the remaining part of the packaging material is folded, and the edge portion is heat-sealed to form the above-mentioned lithium-ion battery (refer to patent document 1).
[0004] However, in order to prevent such multi-layer film packaging materials from being contaminated during their manufacturing process, they are sometimes manufactured by pasting a protective film that is easily peeled off and lightly adhesive on the outside. Among them, in the packaging materials of lithium ion batteries with a matte outer surface, a matte substrate protective layer mixed with particles is arranged on the outer surface. When the battery electrolyte or the like adheres to the surface of the substrate protective layer, its appearance may change. Therefore, packaging materials with such a matte outer surface are usually manufactured by pasting a protective film for protecting the substrate protective layer.
[0005] It should be noted that the protective film is peeled off during the battery manufacturing process or after the battery manufacturing. Therefore, when the lightly adhesive protective film is peeled off, the adhesive used in the protective film does not remain on the outer surface of the packaging material.
[0006] On the other hand, when using the lithium ion battery manufactured as described above, it is bonded and fixed to the electrical device using a double-sided adhesive tape (PSA tape) with strong adhesiveness. Thus, when bonding and fixing it to the electrical device, the PSA tape must be firmly bonded to the outer surface of the packaging material.
[0007] Prior art literature
[0008] Technical Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2013-101765 Summary of the invention
[0010] Problems to be Solved by the Invention
[0011] Therefore, whether the protective film or the PSA tape is an adhesive film or an adhesive tape, one of them (the protective film) needs to be able to be peeled off without leaving any adhesive on the outer surface of the packaging material, and the other (the PSA tape) must be firmly bonded to the outer surface of the packaging material.
[0012] Therefore, an object of the present invention is to provide a packaging material for a power storage device in which the protective film used in the manufacturing process can be peeled off and removed from the outer surface of the packaging material without leaving adhesive residue, and a PSA tape can be firmly adhered to the outer surface of the packaging material thus exposed.
[0013] Means for solving problems
[0014] In order to achieve the above-mentioned object, the present invention provides the following inventions.
[0015] [1] A packaging material for a storage device, comprising, in order from at least the outer surface side, a substrate protective layer, a substrate layer, an adhesive layer, a metal foil layer, and a sealant layer, wherein the substrate protective layer is formed by curing a curable resin mixed with a plurality of particles having different average particle sizes, the curable resin comprising a polyol component as a main agent and a polyisocyanate component as a curing agent, and when among the plurality of particles, particles having a larger average particle size are used as large fillers and particles having a smaller average particle size are used as small fillers, the average particle size of the large filler is 10 μm or more, the average particle size of the small filler is 1 μm or more, and the mixing amount of the large filler accounts for 3% by mass or more of the substrate protective layer, and the mixing amount of the small filler accounts for 5% by mass or more of the substrate protective layer.
[0016] [2] The packaging material for a power storage device according to [1] above, wherein the average particle size of the large filler is 30 μm or less, the average particle size of the small filler is 5 μm or less, and the mixing amount of the large filler is 25 mass % or less.
[0017] [3] The power storage device packaging material according to [1] or [2] above, wherein at least a part of the polyisocyanate component is composed of an alicyclic polyisocyanate.
[0018] [4] A packaging material for a storage device according to any one of [1] to [3] above, wherein at least a portion of the polyisocyanate component is composed of an aliphatic polyisocyanate or an aromatic polyisocyanate, the mixing amount of the large filler is less than 25% by mass, and the total mixing amount of the large filler and the small filler is less than 50% by mass.
[0019] [5] The packaging material for a power storage device according to any one of [1] to [4] above, wherein the macrofiller includes particles of an organic substance.
[0020] [6] The packaging material for a power storage device according to [5] above, wherein the macrofiller includes thermoplastic organic particles, and the thickness of the substrate protection layer is 10 μm or less.
[0021] [7] The packaging material for a power storage device according to any one of [1] to [6] above, wherein the macrofiller includes inorganic particles.
[0022] [8] The packaging material for a power storage device according to any one of [1] to [7] above, wherein a coloring pigment is mixed in the adhesive layer.
[0023] Effects of the Invention
[0024] As will be seen from the experimental examples described below, according to the invention described in [1] above, a lightly adhesive protective film can be peeled off and removed from the outer surface of the packaging material without leaving any adhesive residue, and a strongly adhesive PSA tape can be firmly adhered to the outer surface of the packaging material.
[0025] It should be noted that according to the invention described in [2] above, the outer surface can be formed into a uniform and dense matte state, so that the appearance does not have a rough feel, and a packaging material with excellent appearance can be obtained.
[0026] In addition, according to the invention described in [3] above, the lightly adhesive protective film can be peeled off and removed from the outer surface of the packaging material without leaving adhesive residue, and the strongly adhesive PSA tape can be more firmly adhered to the outer surface of the packaging material.
[0027] In addition, according to the invention described in [4] above, cold forming can be performed without causing cracks or peeling to form a recessed portion for accommodating a battery element. From the viewpoint of more fully achieving this effect, a portion of the polyisocyanate component is composed of an alicyclic polyisocyanate, and a portion can be composed of an aliphatic polyisocyanate or an aromatic polyisocyanate.
[0028] In addition, according to the invention described in [5] above, the thickness of the substrate protective layer can be easily adjusted, and the thickness of the substrate protective layer can be reduced while ensuring the peelability of the protective film and the adhesion of the PSA tape. By reducing the thickness of the substrate protective layer, the process management during cold forming of the packaging material for the storage device can be easily performed. In this case, by setting the thickness of the substrate protective layer within the range described in [6] above, the above effect can be more fully obtained.
[0029] In addition, according to the invention described in [7] above, the gloss of the outer surface will not change due to cold forming, and cold forming can be performed while maintaining a uniform and dense matte outer surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] [ Figure 1 ] Figure 1 It is a schematic cross-sectional view of a specific example of the packaging material for a power storage device of the present invention.
[0031] [ Figure 2 ] Figure 2 The present invention relates to a packaging material for a power storage device after cold forming. Figure 2 (a) is its perspective view; Figure 2 (b) is along Figure 2 (a) is a longitudinal section along line bb.
[0032] [ Figure 3 ] Figure 3 The present invention relates to a specific example of a method for manufacturing an electric storage device. Figure 3 (a) is a perspective view showing a state where a packaging material for a power storage device is prepared, Figure 3 (b) is a perspective view showing a state where a packaging material for a power storage device and a battery element are prepared. Figure 3 (c) is a perspective view of a state where a portion of the packaging material for a power storage device is folded and the end portion is melted, Figure 3 (d) is a perspective view showing a state where both sides of the folded portion are folded upward. DETAILED DESCRIPTION
[0033] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings. It should be noted that in the drawings, the same or corresponding parts are denoted by the same reference numerals, and repeated descriptions are omitted.
[0034] [Electricity storage device packaging materials]
[0035] Figure 1 2 is a cross-sectional view schematically showing an embodiment of a packaging material for a power storage device of the present invention. Figure 1 As shown, the packaging material (packaging material for power storage device) 10 of this embodiment is sequentially stacked with a substrate protection layer 12, a substrate layer 11, a metal foil layer 14, and a sealant layer 17, and anti-corrosion treatment layers 15a and 15b are provided on both sides of the metal foil layer 14. In addition, the substrate layer 11 and the metal foil layer 14 are bonded together via an adhesive layer 13, and the metal foil layer 14 and the sealant layer 17 are bonded together via a sealant adhesive layer 16. It should be noted that in the packaging material 10, the substrate protection layer 12 is used as the outer surface of the power storage device, and the sealant layer 17 is used as the inner surface of the power storage device. The following describes each layer.
[0036] (Base material layer 11)
[0037] The base layer 11 provides heat resistance in the sealing process when manufacturing the power storage device, and plays a role in suppressing the generation of pinholes that may be caused during molding or circulation. In addition, it can also provide scratch resistance, chemical resistance, insulation, etc.
[0038] The base material layer 11 is preferably a layer composed of a resin film formed of an insulating resin. Examples of the resin film include stretched or unstretched films such as polyester films, polyamide films, and polypropylene films. The base material layer 11 may be a single-layer film composed of any one of these resin films, or a laminated film composed of two or more of these resin films.
[0039] Among these films, polyamide films are preferred as the substrate layer 11 from the viewpoint of excellent formability, and biaxially stretched polyamide films are more preferred. Examples of polyamide resins for forming the polyamide film include nylon 6, nylon 6,6, copolymers of nylon 6 and nylon 6,6, nylon 6,10, poly(m-xylylene adipamide) (MXD6), nylon 11, and nylon 12. Among these, nylon 6 (ONy) is preferred from the viewpoint of excellent heat resistance, puncture strength, and impact strength.
[0040] (Base material protection layer 12)
[0041] The base protective layer 12 is located on the outer surface of the packaging material 10 for the storage device, and while protecting the base layer 11, it is bonded to the lightly adhesive protective film used in the battery manufacturing process, and has the function of being easily peeled off without leaving adhesive residue when the protective film is peeled off. In addition, the base protective layer 12 has the function of firmly bonding and fixing the strongly adhesive double-sided tape (PSA tape) when the packaging material 10 for the storage device is bonded and fixed to the electrical equipment.
[0042] In order to exert these effects, the base protective layer 12 needs to be formed by curing a curable resin in which a plurality of types of particles having different average particle diameters are mixed.
[0043] The curable resin contains a polyol component as a main component and a polyisocyanate component as a curing agent.
[0044] Although the polyol component may be any polyol, for example, polyester polyol, acrylic polyol, or polyether polyol may be used. It may also be a mixture of multiple polyols. From the perspective of chemical resistance, adhesion to the substrate layer 11, or film adaptability, polyester polyol or acrylic polyol is preferably used.
[0045] As the polyisocyanate component, a single type of polyisocyanate can be used, or a plurality of polyisocyanates can be mixed and used. In either case, as the polyisocyanate component, alicyclic polyisocyanate can be contained, aliphatic polyisocyanate or aromatic polyisocyanate can be contained, but alicyclic polyisocyanate is preferably contained. It is desirable that a part of the polyisocyanate component is composed of alicyclic polyisocyanate, and the remainder is composed of aliphatic polyisocyanate or aromatic polyisocyanate, and these alicyclic polyisocyanates and aliphatic polyisocyanate or aromatic polyisocyanate are mixed to form the above-mentioned polyisocyanate component.
[0046] It should be noted that, as can be seen from the experimental examples described later, when the polyisocyanate component contains alicyclic polyisocyanate, when the packaging material 10 for the storage device is bonded and fixed to the electrical device, if a PSA tape with strong adhesiveness is used, the PSA tape can be bonded and fixed more firmly than when the alicyclic polyisocyanate is not contained. On the other hand, even when the aliphatic polyisocyanate or aromatic polyisocyanate is not contained, the PSA tape can be bonded and fixed firmly, but cracks may be generated when the packaging material 10 for the storage device is cold-formed.
[0047] As the alicyclic polyisocyanate, for example, methylcyclohexane diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, isopropyl dicyclohexyl-4,4'-diisocyanate, etc. can be used. In addition, as the aliphatic polyisocyanate, for example, hexamethylene diisocyanate can be used. As the aromatic polyisocyanate, meta-xylylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, etc. can be used.
[0048] Next, among the above-mentioned multiple particles with different average particle sizes, the particles with a larger average particle size are used as large fillers, and the particles with a smaller average particle size are used as small fillers. At this time, the large fillers form large bumps on the surface of the substrate protective layer 12, so that the above-mentioned protective film with weak adhesion is bonded in a point contact manner, so that the adhesive used in the protective film can be easily peeled off and removed in a manner that does not remain on the surface of the substrate protective layer 12. For this reason, it is necessary to make the average particle size of the large filler greater than 10μm. In the case where the average particle size of the large filler is smaller than the average particle size, when the above-mentioned protective film is peeled off, the above-mentioned adhesive used in the protective film will remain on the surface of the substrate protective layer 12, that is, remain on the outer surface of the packaging material 10 for the storage device, which may hinder the bonding and fixation of the above-mentioned double-sided tape.
[0049] The average particle size of the macrofiller is preferably 30 μm or less. If the average particle size of the macrofiller is larger than this average particle size, the surface appearance of the base protective layer 12 will not be uniform and dense matte.
[0050] It should be noted that the macrofiller content should be 3% or more by mass of the base protective layer 12. If the macrofiller content is less than this, the adhesive used in the protective film may remain on the surface of the base protective layer 12 when the protective film is peeled off.
[0051] In addition, it is desirable that the blending amount of the macrofiller is 25% by mass or less in the base protective layer 12. When the blending amount of the macrofiller is greater than this, the surface appearance of the base protective layer 12 is not formed into a uniform and dense matte state.
[0052] On the other hand, the small filler forms small concavo-convex shapes on the surface of the base protective layer 12, so that the PSA tape can be firmly bonded and fixed. For this reason, the average particle size of the small filler needs to be 1 μm or more. When the average particle size of the small filler is smaller than this average particle size, the surface appearance of the base protective layer 12 will not become a uniform and dense matte state, and since there are few concavo-convex shapes, the PSA tape cannot be firmly bonded and fixed.
[0053] In addition, it is desirable that the average particle size of the small filler is 5 μm or less. If the average particle size of the small filler is larger than this average particle size, the surface appearance of the base material protection layer 12 will not be uniform and dense matte.
[0054] It should be noted that the mixing amount of the small filler needs to be 5% by mass or more of the base protective layer 12. When the mixing amount of the small filler is less than this mixing amount, the surface appearance of the base protective layer 12 will not become a uniform and dense matte state, and since it has fewer concave and convex surfaces, the above-mentioned PSA tape cannot be firmly bonded and fixed.
[0055] In addition, it is desirable that the mixing amount of the small filler is 45% by mass or less of the base protective layer 12. When the mixing amount of the small filler is more than this mixing amount, the surface appearance of the base protective layer 12 does not form a uniform and dense matte state, and the base protective layer 12 becomes brittle and may crack during cold forming.
[0056] It should be noted that it is desirable that the total mixing amount of these large fillers and small fillers is 50% by mass or less. This is because, when the total mixing amount is greater than the total mixing amount, the base material protective layer 12 becomes brittle, and cracks are easily generated on the base material protective layer during cold forming. In addition, it is desirable that the total mixing amount is 8% by mass or more.
[0057] The materials of such large fillers and small fillers may be arbitrary, for example, organic particles (particles of organic matter) or inorganic particles (particles of inorganic matter) may be used. Examples of organic particles include polyolefin particles such as polyethylene particles, acrylic particles, urethane particles, polyester particles, etc. In addition, inorganic particles include silicon oxide particles, aluminum oxide particles, barium sulfate particles, calcium carbonate particles, titanium oxide particles, etc.
[0058] It should be noted that inorganic particles can be used as macrofillers. When organic particles are used, the macrofiller may be crushed during cold forming, causing gloss changes on the surface of the substrate protective layer 12, i.e., the outer surface of the packaging material 10 for storage devices. In contrast, when inorganic particles are used, gloss changes on the outer surface of the packaging material 10 for storage devices due to cold forming can be suppressed.
[0059] In addition, organic particles can be used as large fillers. When organic particles are used, when the packaging material 10 for the power storage device is made through a lamination process, the organic particles are crushed, and the thickness of the substrate protective layer 12 can be reduced. Thermoplastic organic particles are used among the organic particles, so that the thickness of the packaging material for the power storage device during the product can be easily controlled. As thermoplastic organic particles, polyolefin particles such as polyethylene particles can be used, for example. By reducing the thickness of the substrate protective layer 12, process management such as cold forming can be easily performed. In addition, even if the organic particles are crushed and the contact area with the protective film increases, the adhesion between the organic particles (especially polyethylene particles, etc.) and the weakly adhesive protective film will not increase excessively, and the adhesive used in the protective film will not remain on the surface of the substrate protective layer 12 and be easily peeled off and removed.
[0060] The base protective layer 12 can be formed by dissolving or dispersing the components constituting the base protective layer 12 in a solvent to prepare a coating liquid, and applying the coating liquid on the base protective layer 11 .
[0061] For example, the polyol component may be dissolved in a solvent to form a varnish, and a large filler and a small filler may be mixed in the varnish, and the polyisocyanate component may be mixed to form the coating liquid. Alternatively, the polyol component may be dissolved in a solvent to form a varnish, and a large filler and a small filler may be dispersed in a solvent to produce a slurry, and the slurry may be mixed with the varnish, and the polyisocyanate component may be mixed to form the coating liquid.
[0062] It should be noted that, in addition to the above, the coating liquid may also contain additives such as flame retardants, lubricants, antioxidants, light stabilizers, tackifiers, leveling agents, defoamers, catalysts, and reaction delay agents. Examples of lubricants include fatty acid amides such as oleamide, erucamide, stearamide, behenamide, ethylenebisoleamide, and ethylenebiserucamide. In addition, examples of reaction delay agents include acetylacetone.
[0063] As the coating method, a gravure direct coating method, a gravure reverse coating method, a micro gravure coating method, or the like can be used.
[0064] The thickness of the substrate protective layer 12 can be 0.5 μm or more, 1.0 μm or more, or 1.5 μm or less, 50 μm or less, 30 μm or less, 15 μm or less, or 10 μm or less. When the thickness is above the lower limit, the function of protecting the substrate layer 11, the function of easily peeling off without leaving adhesive residue when peeling off the lightly adhesive protective film, and the function of firmly bonding and fixing the strongly adhesive PSA tape cannot be obtained more fully. In addition, when the thickness is below the upper limit, the overall thickness of the packaging material 10 for the storage device can be made thinner, and the process management of the packaging material 10 for the storage device can be easily performed when cold forming. It should be noted that in the case where the substrate protective layer 12 contains thermoplastic organic particles as a large filler, the organic particles are crushed in the lamination process when making the packaging material 10 for the storage device, and the thickness of the substrate protective layer 12 tends to be thinner. Therefore, in the case where the macrofiller includes thermoplastic organic particles or consists only of thermoplastic organic particles, the thickness of the substrate protection layer 12 may be 10 μm or less, 8 μm or less, or 6 μm or less.
[0065] (Adhesive layer 13)
[0066] The adhesive layer 13 is a layer that bonds the base layer 11 and the metal foil layer 14. The adhesive layer 13 has the adhesion required to firmly bond the base layer 11 and the metal foil layer 14 together, and also has the followability to suppress the metal foil layer 14 from breaking due to the base layer 11 during cold forming (even if the component is deformed or stretched, it will not peel off, but the adhesive layer 13 is reliably formed on the component).
[0067] As the adhesive constituting the adhesive layer 13, for example, a two-component curing polyurethane adhesive having a main agent composed of a polyol such as polyester polyol, polyether polyol, acrylic polyol, etc., and a curing agent composed of an isocyanate such as an aromatic or aliphatic isocyanate can be used. In the above adhesive, the molar ratio (=NCO / OH) of the isocyanate group of the curing agent to the hydroxyl group of the main agent is preferably 1 to 50, more preferably 2 to 30.
[0068] After application, the polyurethane adhesive is aged at, for example, 4 days or more at 40° C. so that the hydroxyl group of the main agent and the isocyanate group of the curing agent can react, thereby making the base material layer 11 and the metal foil layer 14 bonded together more firmly.
[0069] It should be noted that the adhesive may also be mixed with a coloring pigment, such as a black pigment. By mixing a coloring pigment in the adhesive to form the bonding layer 13, the packaging material 10 for the storage device is colored with the color, and the appearance of the storage device using the packaging material 10 for the storage device is also colored with the color, which can improve its design.
[0070] (Metal foil layer 14)
[0071] As the metal foil layer 14, various metal foils such as aluminum and stainless steel can be cited. From the perspective of workability such as moisture resistance and ductility and cost, the metal foil layer 14 is preferably aluminum foil. The aluminum foil may be a general soft aluminum foil, but from the perspective of excellent pinhole resistance and ductility during molding, an iron-containing aluminum foil is preferred.
[0072] (Anti-corrosion treatment layers 15a, 15b)
[0073] The anti-corrosion treatment layers 15a and 15b play a role in suppressing the corrosion of the metal foil layer 14 caused by fluoric acid generated by the electrolyte or the reaction between the electrolyte and water. In addition, the anti-corrosion treatment layer 15a plays a role in improving the adhesion between the metal foil layer 14 and the adhesive layer 13. In addition, the anti-corrosion treatment layer 15b plays a role in improving the adhesion between the metal foil layer 14 and the sealant adhesive layer 16. The anti-corrosion treatment layer 15a and the anti-corrosion treatment layer 15b can be layers of the same composition or layers of different compositions.
[0074] The anti-corrosion treatment layers 15a, 15b can be formed by performing an anti-corrosion treatment on the metal foil layer 14. The anti-corrosion treatment may be, for example, a degreasing treatment, a hydrothermal modification treatment, an anodizing treatment, a chemical conversion treatment, a coating-type anti-corrosion treatment of applying a coating agent having anti-corrosion ability; or a combination of these treatments.
[0075] (Sealing agent bonding layer 16)
[0076] The sealant adhesive layer 16 is a layer that bonds the metal foil layer 14 formed with the anticorrosion treatment layer 15b to the sealant layer 17. The sealant adhesive layer 16 may be made of a dry lamination adhesive or a melt adhesive resin. In the sealant adhesive layer 16, a general adhesive for bonding the metal foil layer 14 to the sealant layer 17 may be used. As a method for laminating the metal foil layer 14 and the sealant layer 17 via the sealant adhesive layer 16, for example, the following methods may be used: a dry lamination method using a dry lamination adhesive such as a polyurethane adhesive; or an extrusion lamination method or a sandwich lamination method using an acid-modified polyolefin.
[0077] (Sealing agent layer 17)
[0078] The sealant layer 17 is a layer that imparts heat sealability to the packaging material 10 for the storage device, and is a layer that is arranged inside and heat-fused when the storage device is assembled. As the sealant layer 17, a resin film composed of a polyolefin resin or an acid-modified polyolefin resin in which an acid such as maleic anhydride is graft-modified in the polyolefin resin can be cited. Among these, a polyolefin resin that can improve the barrier property of water vapor, does not deform excessively due to heat sealing, and can form the shape of the storage device is preferred, and polypropylene is particularly preferred.
[0079] (Method for Manufacturing Power Storage Device Outer Material 10)
[0080] Next, a method for producing the power storage device packaging material 10 will be described. It should be noted that the production method is not limited to the following method.
[0081] As a method for producing the power storage device packaging material 10 , for example, there can be mentioned a method including the following steps S11 to S14 , and producing in the order of S11 , S12 , S13 , and S14 .
[0082] Step S11 : a step of forming the anti-corrosion treatment layer 15 a on one surface of the metal foil layer 14 and forming the anti-corrosion treatment layer 15 b on the other surface of the metal foil layer 14 .
[0083] Step S12 : a step of bonding the surface of the anticorrosion treatment layer 15 a opposite to the metal foil layer 14 and the base material layer 11 together via the adhesive layer 13 .
[0084] Step S13 : a step of forming the base protective layer 12 by coating on the surface of the base layer 11 opposite to the adhesive layer 13 .
[0085] Step S14 : a step of forming a sealant layer 17 on the surface of the anticorrosion treated layer 15 b opposite to the metal foil layer 14 via a sealant adhesive layer 16 .
[0086] [Method for manufacturing power storage device]
[0087] Next, a method for manufacturing an electricity storage device using the electricity storage device packaging material 10 will be described. Figure 3 (a) to (d) are perspective views showing the manufacturing process of a single-side molding battery. Figure 2 The power storage device packaging material 10 after cold forming is shown.
[0088] The secondary battery 20 as a single-side molded battery can be manufactured, for example, through the following steps S21 to S28. The secondary battery 20 manufactured through the steps can be firmly bonded and fixed to an electrical device via a strongly adhesive double-sided tape (PSA tape).
[0089] Step S21: a step of preparing the packaging material 10 for a power storage device, the battery element 1 including electrodes, and the leads 2 extending from the electrodes.
[0090] Step S22: A step of cold-forming the recessed portion 10a for arranging the battery element 1 on one side of the packaging material 10 for a storage battery device (see Figure 3 (a) and Figure 3 (b)).
[0091] Step S23: a step of placing the battery element 1 in the recess 10a of the packaging material 10 for a storage device having the recess 10a formed therein, folding the packaging material 10 for a storage device so that the lid 10b covers the recess 10a, and heat-sealing one side of the packaging material 10 for a storage device by applying pressure so as to sandwich the lead 2 extending from the battery element 1 (see Figure 3 (b) and Figure 3 (c)).
[0092] Step S24: a step of attaching a protective film to the power storage device packaging material 10 .
[0093] Step S25: A step of manufacturing the battery 20 by retaining one side except the side holding the lead 2, performing heat-fusion bonding under pressure on the other sides, injecting electrolyte from the retained side, and performing heat-fusion bonding under pressure on the retained side in a vacuum state (see Figure 3 (c)).
[0094] Step S26: a step of setting the current value, voltage value, ambient temperature, etc. to predetermined conditions, performing charging and discharging, and causing chemical changes.
[0095] Step S27 : a step of peeling and removing the protective film from the power storage device packaging material 10 .
[0096] Step S28: A step of cutting off the end of the pressurized heat-welded side except the side holding the lead wire 2 and bending it toward the concave portion 10a (see Figure 3 (d)).
[0097] Example
[0098] Hereinafter, the present invention will be described based on Examples and Comparative Examples. It should be noted that, for the sake of convenience, Examples and Comparative Examples are not distinguished, but are all referred to as Experimental Examples.
[0099] These experimental examples can be divided into experimental example groups 1 to 22. Therefore, each experimental example group is explained and examined, and finally the examination of these experimental examples is summarized.
[0100] In these experimental examples, nylon film was used as the base layer 11. A 35 μm thick aluminum having anticorrosion treatment layers 15a and 15b on both sides was used as the metal foil layer 14. A 35 μm thick polypropylene film was used as the sealant layer 17. The base protective layer 12 will be described later.
[0101] Then, first, the base material layer 11 and the metal foil layer 14 are bonded together using a heat-sensitive adhesive (step S12).
[0102] Next, the base protective layer 12 is formed by coating on the surface of the base layer 11 (step S13 ).
[0103] Next, the sealant adhesive layer 16 and the sealant layer 17 are formed on the metal foil layer 14 by a co-extrusion method, thereby manufacturing the packaging material 10 for a power storage device (step S14 ).
[0104] Next, before describing the base protective layer 12 of each experimental example, the evaluation method of these experimental examples will be described. These experimental examples were evaluated from the following five viewpoints.
[0105] <Evaluation method>
[0106] (Appearance of coating film)
[0107] After the above-mentioned substrate protective layer 12 is formed by coating (the above-mentioned step S13), the appearance of the substrate protective layer 12 is observed with the naked eye, and the case where a uniform and dense matte appearance without roughness can be observed is evaluated as "A"; the case where a smooth appearance and a roughness are observed is evaluated as "F".
[0108] (PSA seal)
[0109] In the obtained packaging material, a strong adhesive double-sided tape was pasted on the sealant layer 17, and then pasted on the metal plate through the double-sided tape. Next, a PSA tape with a width of 10 mm was pasted on the base protective layer 12, and an aluminum foil was pasted through the PSA tape. Then, after leaving it at room temperature for 2 hours, a tensile tester was used to perform 180-degree peeling at a speed of 300 mm / min to measure the peel strength between the base protective layer 12 and the PSA tape.
[0110] The case where the peel strength was 5 N / 10 mm or more was evaluated as "A", the case where it was 2.5 N / 10 mm or more and less than 5 N / 10 mm was evaluated as "B", and the case where it was less than 2.5 N / 10 mm was evaluated as "F".
[0111] (Protective film paste residue)
[0112] A strongly adhesive double-sided tape is pasted on the sealant layer 17 of the obtained packaging material 10, and then pasted on the metal plate via the double-sided tape. Next, a weakly adhesive protective film is pasted on the above-mentioned substrate protective layer 12. Then, it is kept at a temperature of 85°C for 6 hours, cooled and restored to room temperature, and then a tensile tester is used to perform a 180-degree peeling between the above-mentioned substrate protective layer 12 and the protective film at a speed of 300 mm / min, and it is confirmed whether the adhesive of the protective film remains on the surface of the substrate protective layer 12. The situation where no adhesive residue is observed is evaluated as "A"; the situation where residue is observed is evaluated as "F".
[0113] (Appearance after molding)
[0114] A recess 10a is cold-formed in the packaging material 10 for a storage device (the above-mentioned step S22). The depth of the recess 10a is 3.5 mm. Then, by visual observation, it is evaluated whether cracks are generated in the substrate protective layer 12 and whether the gloss changes. The situation where no cracks are generated and the gloss remains the state before cold forming is evaluated as "A". The situation where no cracks are generated but the gloss changes, and a part of it has a glossy feeling (increased gloss) is evaluated as "B". In addition, the situation where cracks are generated in the substrate protective layer 12 is evaluated as "F".
[0115] (film thickness)
[0116] The film thickness of the base protective layer 12 in the obtained packaging material 10 was measured using a contact thickness measuring device (trade name: Picoco, manufactured by Ozaki Manufacturing Co., Ltd.). The difference between the thickness of the obtained packaging material 10 and the thickness of the packaging material sample without the base protective layer 12 formed thereon was defined as the film thickness of the base protective layer 12.
[0117] <First Experimental Group and Its Investigation>
[0118] The first experimental example group consists of experimental examples 1-1 to 1-5. In this experimental example group, the main agent is set to polyester polyol, and the curing agent is set to hexamethylene diisocyanate (HDI) and isophorone diisocyanate (IPDI). It should be noted that HDI is an aliphatic polyisocyanate, and IPDI is an alicyclic polyisocyanate. Then, the mixing ratio of HDI and IPDI is HDI:IPDI is 9:1 by mass ratio.
[0119] In addition, in this experimental example group, silicon oxide particles having an average particle diameter of 15 μm were used as a macrofiller, and 10% by mass of the silicon oxide particles were mixed with respect to the base protective layer 12 .
[0120] In this experimental example group, silicon oxide particles were used as the small filler, and the silicon oxide particles were mixed in an amount of 20 mass % with respect to the base material protection layer 12 .
[0121] Then, in each experimental example, by using small fillers with different average particle sizes, the relationship between the average particle size of the small fillers and the above-mentioned evaluation items was studied. The results are shown in Table 1.
[0122] [Table 1]
[0123]
[0124] (Appearance of coating film)
[0125] From this result, it can be seen that under the above conditions, when the average particle size of the small filler is 1 to 5 μm, a uniform and dense matte substrate protective layer without roughness can be formed. It should be noted that in Experimental Examples 1-4, since the average particle size of the small filler is smaller than the above average particle size, the surface of the substrate protective layer is small and does not become matte. In addition, in Experimental Examples 1-5, the surface of the substrate protective layer becomes matte, but since the average particle size of the small filler is large, the surface of the substrate protective layer is large and does not become uniform and dense. Matte.
[0126] (PSA seal)
[0127] From this result, it is understood that under the above-mentioned conditions, when the average particle size of the small filler is 1 μm or more, the PSA tape adheres strongly.
[0128] (Protective film paste residue)
[0129] It can be considered that under the above conditions, the average particle size of the small filler has nothing to do with the residual paste of the protective film, and no matter what the average particle size is, no residual paste will be generated.
[0130] (Appearance after molding)
[0131] It can be seen that under the above conditions, the average particle size of the small filler has nothing to do with the appearance after molding. Regardless of the average particle size, no cracks will be generated on the substrate protective layer, and no gloss change will be caused.
[0132] <Second Experimental Group and Its Investigation>
[0133] The second experimental example group consists of experimental example 2-1. In this second experimental example group, a large filler with a smaller average particle size is used and compared with the first experimental example group, so as to study the relationship between the average particle size of the large filler and the above-mentioned evaluation items. That is, the average particle size of the large filler used in experimental example 2-1 is 5μm, and the packaging material 10 for the storage device is manufactured in the same manner as experimental example 1-2, and the above-mentioned evaluation items are studied. The results are shown in Table 2.
[0134] [Table 2]
[0135]
[0136] (Appearance of coating film)
[0137] From this result, it can be seen that even when the average particle size of the macrofiller is set to 5 μm, the coating film appearance does not change. That is, similarly to Experimental Example 1-2, a uniform and dense matte substrate protective layer without a rough feeling can be formed.
[0138] (PSA seal)
[0139] It is considered that even when the average particle size of the macro filler was set to 5 μm, the PSA tape adhered strongly as in Experimental Example 1-2.
[0140] (Protective film paste residue)
[0141] When the large filler was reduced to an average particle size of 5 μm, unlike Experimental Example 1-2, the adhesive of the protective film remained on the surface of the base protective layer 12. Therefore, it can be considered that the average particle size of the large filler is related to the residual paste of the protective film, and in order to prevent the generation of residual paste under the above conditions, the average particle size of the large filler can be set to 15 μm (Experimental Example 1-3).
[0142] (Appearance after molding)
[0143] It is found that even when the average particle size of the macro filler was set to 5 μm, similarly to Experimental Example 1-2, no cracks were generated in the base protective layer and no change in gloss was caused.
[0144] <The third experimental group and its investigation>
[0145] In the first experimental example group in which the average particle size of the large filler was set to 15 μm, no protective film paste residue was generated, but in the second experimental example group in which the average particle size was set to 5 μm, protective film paste residue was generated. Therefore, in the third experimental example group, large fillers having average particle sizes between these were used to study the relationship between the average particle size of the large filler and the above-mentioned evaluation items. That is, the average particle size of the large filler used in the third experimental example group was 10 μm.
[0146] In addition, in each experimental example, by using small fillers having different average particle diameters, the relationship between the average particle diameter of the small fillers and the above-mentioned evaluation items when a large filler having an average particle diameter of 10 μm was used was examined.
[0147] It should be noted that in the first experimental example group, when the average particle size of the small filler was 0.1 μm (Experimental Example 1-4) and 10 μm (Experimental Example 1-5), the evaluation of the coating appearance and the PSA adhesion was poor. Therefore, in contrast, when the average particle size of the small filler was 5 μm (Experimental Example 3-1), 3 μm (Experimental Example 3-2), and 1 μm (Experimental Example 3-3), the packaging material 10 for the storage device was manufactured and the above-mentioned evaluation items were studied. The results are shown in Table 3.
[0148] [Table 3]
[0149]
[0150] (Appearance of coating film)
[0151] The results show that even when the average particle size of the large filler was 10 μm, the coating film appearance did not change, and a uniform and dense matte substrate protection layer without roughness was formed similarly to Experimental Example Group 1. Furthermore, the average particle size of the small filler was irrelevant.
[0152] (PSA seal)
[0153] It is considered that even when the average particle size of the large filler was 10 μm, the PSA tape adhered strongly as in Experimental Example Group 1. The average particle size of the small filler was irrelevant.
[0154] (Protective film paste residue)
[0155] Even when the average particle size of the large filler was 10 μm, no paste residue was generated. The average particle size of the small filler was irrelevant.
[0156] Considering the results of the third experimental example group in addition to the results of the first and second experimental example groups, it can be considered that in order to prevent the paste from remaining, the average particle size of the large filler only needs to be 10 μm or more.
[0157] (Appearance after molding)
[0158] It is found that even when the average particle size of the large filler is 10 μm, no cracks are generated in the base protective layer and no change in gloss occurs, similar to Experimental Example Group 1. The average particle size of the small filler is irrelevant.
[0159] <Fourth Experimental Group and Its Investigation>
[0160] In the fourth experimental example group, the average particle size of the large filler was increased to study the relationship between the average particle size of the large filler and the above-mentioned evaluation items. That is, the average particle size of the large filler used in the fourth experimental example group was 30 μm.
[0161] In addition, in each experimental example, small fillers with different average particle sizes were used to study the relationship between the average particle size of the small fillers and the above evaluation items when a large filler with an average particle size of 30 μm was used. It should be noted that the average particle sizes of the small fillers were 5 μm (Experimental Example 4-1), 3 μm (Experimental Example 4-2), and 1 μm (Experimental Example 4-3).
[0162] The results of the above evaluation items are shown in Table 4.
[0163] [Table 4]
[0164]
[0165] (Appearance of coating film)
[0166] The results show that even when the average particle size of the large filler was 30 μm, the coating film appearance did not change, and a uniform and dense matte substrate protection layer without roughness was formed similarly to Experimental Example Group 1. The average particle size of the small filler was irrelevant.
[0167] (PSA seal)
[0168] It is considered that even when the average particle size of the large filler was 30 μm, the PSA tape adhered strongly as in Experimental Example Group 1. The average particle size of the small filler was irrelevant.
[0169] (Protective film paste residue)
[0170] Even when the average particle size of the large filler was 30 μm, no paste residue was generated. The average particle size of the small filler was irrelevant.
[0171] (Appearance after molding)
[0172] It is found that even when the average particle size of the large filler is 30 μm, no cracks are generated in the base protective layer and no change in gloss occurs, similar to Experimental Example Group 1. The average particle size of the small filler is irrelevant.
[0173] <Fifth Experimental Group and Its Investigation>
[0174] In the fifth experimental example group, the average particle size of the large filler was further increased, and the relationship between the average particle size of the large filler and the above-mentioned evaluation items was studied. That is, the average particle size of the large filler used in the fifth experimental example group was 50 μm.
[0175] The fifth experimental example group consists of Experimental Example 5-1. Specifically, the packaging material 10 for a power storage device was produced in the same manner as Experimental Example 1-2 except that the average particle size of the macrofiller used in Experimental Example 5-1 was 50 μm, and the above-mentioned evaluation items were studied. The results are shown in Table 5.
[0176] [Table 5]
[0177]
[0178] (Appearance of coating film)
[0179] The results show that when the average particle size of the macrofiller is 50 μm, a uniform and dense matte substrate protection layer without roughness cannot be formed. That is, the surface of the substrate protection layer becomes matte with roughness due to the large average particle size of the macrofiller.
[0180] Therefore, it can be considered that in order to form a uniform and dense matte substrate protection layer without roughness, in addition to setting the average particle size of the small filler to 1 to 5 μm (refer to the investigation of the first experimental example group), the average particle size of the large filler should also be set to 30 μm or less.
[0181] (PSA seal)
[0182] It is considered that even when the average particle size of the macro filler was 50 μm, the PSA tape adhered strongly as in Experimental Example 1-2.
[0183] (Protective film paste residue)
[0184] Even when the average particle size of the macrofiller was set to 50 μm, no paste residue was generated similarly to Experimental Example 1-2.
[0185] (Appearance after molding)
[0186] It was found that even when the average particle size of the macro filler was 50 μm, similarly to Experimental Example 1-2, no cracks were generated in the base protective layer and no change in gloss was caused.
[0187] <Sixth Experimental Group and Its Investigation>
[0188] In the sixth experimental example group, the relationship between the mixing amount of the large filler and the above-mentioned evaluation items was studied by changing the mixing amount of the large filler. That is, in the sixth experimental example group, the mixing amount of the large filler in the substrate protective layer was 1 mass % (experimental example 6-1), 3 mass % (experimental example 6-2), 25 mass % (experimental example 6-3) and 30 mass % (experimental example 6-4), and the packaging material 10 for the storage device was manufactured in the same manner as in the experimental example 1-2, and the above-mentioned evaluation items were studied. The results are shown in Table 6.
[0189] [Table 6]
[0190]
[0191] (Appearance of coating film)
[0192] In Experimental Example 6-4, the surface of the substrate protective layer became matte with a rough feel due to the excessive mixing amount of the large filler. From this result, it can be considered that in addition to setting the average particle size of the small filler to 1 to 5 μm and the average particle size of the large filler to 30 μm or less (refer to the investigation of the first and fifth experimental example groups), the mixing amount of the large filler should be set to 25% by mass or less.
[0193] (PSA seal)
[0194] It is considered that when the compounding amount of the macrofiller is within the range of 1 to 30% by mass, the PSA tape adheres firmly as in Experimental Example 1-2.
[0195] (Protective film paste residue)
[0196] In Experimental Example 6-1, since the mixing amount of the large filler was too small, the adhesive of the protective film remained on the surface of the base protective layer 12. From this result, it can be considered that in order to prevent the adhesive of the protective film from remaining as a paste, in addition to setting the average particle size of the large filler to 10 μm or more (refer to the investigation of the third experimental example group), it is also necessary to set the mixing amount to 3 mass % or more.
[0197] (Appearance after molding)
[0198] It is considered that when the blending amount of the macrofiller is within the range of 1 to 30 mass %, similarly to Experimental Example 1-2, no cracks are generated in the base protective layer and no change in gloss is caused.
[0199] <Seventh Experimental Group and Its Investigation>
[0200] In the seventh experimental example group, the mixing amount of the large filler was set to 30 mass % and the mixing amount of the small filler was changed to examine the relationship between the total mixing amount of the large filler and the small filler and the above-mentioned evaluation items.
[0201] It should be noted that in this experimental example group, the average particle size of the large filler was changed at the same time, but the average particle size was made 10μm and 15μm. From the investigation of the above-mentioned experimental example groups 1 to 6, it can be seen that this degree of difference in average particle size will not affect the results of each evaluation item.
[0202] In addition, experimental examples in which the relationship between the total mixing amount and the above-mentioned evaluation items was examined by setting the mixing amount of the large filler to less than 30 mass % and changing the mixing amount of the small filler will be described later as Experimental Example Groups 8 and 9.
[0203] That is, the large filler used in Experimental Example 7-1 had an average particle size of 15 μm and a mixing amount of 30 mass %, and the mixing amount of the small filler was 30 mass %. The total mixing amount was 60 mass %. Then, the power storage device packaging material 10 was manufactured in the same manner as Experimental Example 1-2 except for the above.
[0204] In Experimental Example 7-2, the large filler used had an average particle size of 10 μm and its blending amount was 30% by mass, and the blending amount of the small filler was 20% by mass. The total blending amount was 50% by mass.
[0205] The results of the above evaluation items are shown in Table 7.
[0206] [Table 7]
[0207]
[0208] (Appearance of coating film)
[0209] Since the amount of macrofiller mixed was too much, the surface of the substrate protective layer became matte with a rough feel in both Experimental Example 7-1 and Experimental Example 7-2. The relationship between the total amount of mixed and the appearance of the coating film could not be evaluated in this experimental example group.
[0210] (PSA seal)
[0211] It is considered that even when the total blending amount was 50 to 60% by mass, the PSA tape adhered strongly as in Experimental Example 1-2.
[0212] (Protective film paste residue)
[0213] It is considered that even when the total mixing amount was set to 50 to 60% by mass, similarly to Experimental Example 1-2, no adhesive residue of the protective film was generated.
[0214] (Appearance after molding)
[0215] In Experimental Example 7-1, in which the mixing amount of the small filler was set to 30 mass % and the total mixing amount was set to 60 mass %, cracks occurred in the base protective layer after cold forming. Whether the reason was due to excessive mixing amount of the small filler or excessive total mixing amount was not clear in this Experimental Example Group 7. However, by simultaneously examining the Experimental Example Groups 8 and 9 described below, it can be seen that the main cause of the poor appearance after forming is the total mixing amount.
[0216] <The 8th Experimental Group and Its Investigation>
[0217] In the eighth experimental example group, the average particle size of the large filler was set to 15 μm, the mixing amount thereof was set to 3 mass %, and the mixing amount of the small filler was changed to study the relationship between the total mixing amount of the large filler and the small filler and the above-mentioned evaluation items. Then, except for this, the packaging material 10 for the storage device was manufactured in the same manner as in Experimental Example 1-2.
[0218] The results of the above evaluation items are shown in Table 8.
[0219] [Table 8]
[0220]
[0221] (Appearance of coating film)
[0222] In Experimental Example 8-1, since the mixing amount of the small filler is small (2% by mass) and the total mixing amount is also small (5% by mass), the appearance of the substrate protective layer 12 does not become a uniform and dense matte state, but becomes smooth. In the experimental example where the mixing amount of the small filler is 5% by mass or more and the total mixing amount is 8% by mass or more, it becomes a matte state that is not rough, uniform and dense. Therefore, it can be considered that in order to make the appearance of the substrate protective layer 12 uniform and dense matte, it is sufficient to set the mixing amount of the small filler to 5% by mass or more and the total mixing amount to 8% by mass or more. It should be noted that whether the reason for the smooth appearance of the substrate protective layer 12 is the mixing amount of the small filler or the total mixing amount is not clear in this experimental example group.
[0223] (PSA seal)
[0224] Similarly, in Experimental Example 8-1, the PSA tape was not firmly adhered due to the small amount of small fillers mixed (2% by mass) and the small total amount (5% by mass). In the experimental examples where the amount of small fillers mixed was 5% by mass or more and the total amount was 8% by mass or more, high peel strength was shown. Therefore, it can be considered that in order to make the PSA tape firmly adhere to the substrate protective layer 12, in addition to setting the average particle size of the small fillers to 1 μm or more (refer to the investigation of the first experimental example group), the amount of small fillers mixed was set to 5% by mass or more and the total amount was set to 8% by mass or more. Whether the reason is the amount of small fillers mixed or the total amount of mixed is not clear in this experimental example group.
[0225] (Protective film paste residue)
[0226] It is considered that even if the total blending amount is set to 5 to 53% by mass, no adhesive paste residue of the protective film is generated.
[0227] (Appearance after molding)
[0228] In Experimental Example 8-6, in which the mixing amount of the small filler was set to 50 mass % and the total mixing amount was set to 53 mass %, cracks occurred in the base protective layer after cold forming. Whether the reason was due to excessive mixing amount of the small filler or excessive total mixing amount was not clear in this Experimental Example Group 8.
[0229] <9th Experimental Group and Its Investigation>
[0230] In the ninth experimental example group, the average particle size of the large filler was set to 15 μm, the mixing amount thereof was set to 25 mass %, and the mixing amount of the small filler was changed to study the relationship between the total mixing amount of the large filler and the small filler and the above-mentioned evaluation items. Then, except for this, the packaging material 10 for the storage device was manufactured in the same manner as in Experimental Example 1-2.
[0231] The results of the above evaluation items are shown in Table 9.
[0232] [Table 9]
[0233]
[0234] (Appearance of coating film)
[0235] In Experimental Example 9-1, since the mixing amount of the small filler is small (2 mass %), the appearance of the base protective layer 12 is not uniform and dense matte, but becomes smooth. It should be noted that in Experimental Example 9-1, the total mixing amount is 27 mass %, so by simultaneously examining the above-mentioned Experimental Example Group 8, it can be inferred that the reason why the base protective layer 12 becomes smooth is mainly due to the mixing amount of the small filler.
[0236] On the other hand, in the experimental examples where the mixing amount of the small filler was 5 mass % or more, since the surface was not rough but uniform and dense matte, it can be inferred that the mixing amount of the small filler can be set to 5 mass % or more.
[0237] (PSA seal)
[0238] Similarly, in Experimental Example 9-1, since the mixing amount of the small filler was small (2% by mass), the PSA tape did not adhere strongly. It is estimated that the main reason for this is the mixing amount of the small filler.
[0239] In addition, high peel strength was shown in the experimental examples in which the mixing amount of small fillers was 5% by mass or more. Therefore, it can be inferred that in order to make the PSA tape firmly adhere to the substrate protective layer 12, in addition to setting the average particle size of the small filler to be greater than 1 μm (refer to the investigation of the first experimental example group), the mixing amount of the small filler should also be set to greater than 5% by mass.
[0240] (Protective film paste residue)
[0241] It is believed that even when the total mixing amount is 27 to 75% by mass, no adhesive residue of the protective film occurs. By also examining the eighth experimental example group, it is believed that the total mixing amount and the adhesive residue of the protective film have a weak correlation.
[0242] (Appearance after molding)
[0243] In Experiment 9-6, in which the mixing amount of the small filler was 45 mass % and the total mixing amount was 70 mass %, cracks occurred in the base protective layer after cold forming. In Experiment 8-5, although the mixing amount of the small filler was 45 mass %, no cracks occurred in the base protective layer and no change in gloss was caused, so it can be considered that the cause of the cracks is the total mixing amount.
[0244] In addition, in the experimental examples where the total mixing amount was 50 mass % or less, no cracks were generated and no change in gloss was caused. Therefore, it can be considered that in order to obtain a good appearance after molding, the total mixing amount of the large filler and the small filler only needs to be set to 50 mass % or less.
[0245] <10th Experimental Group and Its Investigation>
[0246] In the 10th experimental example group, the polyisocyanate component of the curable resin was changed, and the relationship between the type of the polyisocyanate component and the above-mentioned evaluation items was studied. Then, the packaging material 10 for the storage device was manufactured in the same manner as in Experimental Example 1-1. It should be noted that in Experimental Example 10-1, the mixing ratio of toluene diisocyanate (TDI) and IPDI was 9:1 in terms of mass ratio of TDI:IPDI.
[0247] The results of the above evaluation items are shown in Table 10.
[0248] [Table 10]
[0249]
[0250] (Appearance of coating film)
[0251] From this result, it is understood that the coating film appearance does not depend on the type of the polyisocyanate component.
[0252] (PSA seal)
[0253] In Experiment 10-2 using only aliphatic polyisocyanate (HDI) as the polyisocyanate component and Experiment 10-4 using only aromatic polyisocyanate (TDI) as the polyisocyanate component, it was observed that the peel strength of the PSA tape decreased. It was not firmly bonded. In contrast, in Experiments 10-1 and 10-3 using alicyclic polyisocyanate (IPDI) as at least a portion of the polyisocyanate component, high peel strength was shown, so it can be considered that: in order to make the PSA tape firmly bonded to the substrate protective layer 12, in addition to setting the average particle size of the small filler to 1 μm or more and its mixing amount to 5% by mass or more (refer to the investigation of the first and ninth experimental example groups), it is important to use alicyclic polyisocyanate as at least a portion of the polyisocyanate component.
[0254] (Protective film paste residue)
[0255] It is considered that the adhesive paste residue of the protective film does not depend on the type of the polyisocyanate component.
[0256] (Appearance after molding)
[0257] In Experimental Example 10-3, in which only alicyclic polyisocyanate (IPDI) was used as the polyisocyanate component, cracks occurred in the substrate protective layer after cold forming. In contrast, in Experimental Examples 10-1, 10-2, and 10-4, in which at least a portion of the polyisocyanate component used aliphatic polyisocyanate (HDI) or aromatic polyisocyanate (TDI), cracks did not occur in the substrate protective layer, and no gloss change occurred. Therefore, it can be seen that in order to obtain a good appearance after forming, it is sufficient to use aliphatic polyisocyanate or aromatic polyisocyanate as at least a portion of the polyisocyanate component.
[0258] <11th Experimental Group and Its Investigation>
[0259] In the 11th experimental example group, by changing the material of the large filler and the material of the small filler, the relationship between the material of these fillers and the above-mentioned evaluation items was studied. Then, except for this, the packaging material 10 for the storage device was manufactured in the same manner as in Experimental Example 1-1. It should be noted that in Experimental Example 11-1, organic particles (carbamate particles) were used as large fillers and small fillers. In addition, in Experimental Example 11-2, inorganic particles (silicon oxide particles) were used as large fillers, and organic particles (carbamate particles) were used as small fillers. In Experimental Example 11-3, on the contrary, organic particles (carbamate particles) were used as large fillers, and inorganic particles (silicon oxide particles) were used as small fillers.
[0260] The results of the above evaluation items are shown in Table 11.
[0261] [Table 11]
[0262]
[0263] (Appearance of coating film)
[0264] From this result, it is understood that the coating film appearance does not depend on the material of these fillers.
[0265] (PSA seal)
[0266] The adhesion of PSA tape will not change significantly due to the material of these fillers.
[0267] (Protective film paste residue)
[0268] The adhesive residue of the protective film does not depend on the material of these fillers.
[0269] (Appearance after molding)
[0270] In Experimental Examples 11-1 and 11-3, which used organic particles (urethane particles) as macrofillers, the macrofillers were crushed during cold forming, and gloss (glossiness) was generated on the substrate protective layer 12. In contrast, in Experimental Example 11-2 or the above-mentioned Experimental Example Group 1, which used inorganic particles (silicon oxide particles) as macrofillers, such gloss (glossiness) was not generated.
[0271] Therefore, it is considered that in order to prevent the gloss change caused by cold forming, it is sufficient to use inorganic particles as a macrofiller.
[0272] <12th to 21st experimental groups and their investigation>
[0273] In Experimental Example Groups 12 to 21, the polyol component of the curable resin was set to polyacrylic polyol having a glass transition temperature of 50 to 60° C., and Experimental Example Groups 1 to 10 were repeated. The results of the above evaluation items are shown in Tables 12 to 21.
[0274] [Table 12]
[0275]
[0276] [Table 13]
[0277]
[0278] [Table 14]
[0279]
[0280] [Table 15]
[0281]
[0282] [Table 16]
[0283]
[0284] [Table 17]
[0285]
[0286] [Table 18]
[0287]
[0288] [Table 19]
[0289]
[0290] [Table 20]
[0291]
[0292] [Table 21]
[0293]
[0294] The results of the above-mentioned evaluation items were the same as those of Experimental Example Groups 1 to 10. Therefore, it can be considered that any evaluation item is independent of the type of the polyol component.
[0295] <22nd Experimental Group and Its Investigation>
[0296] In the 22nd experimental example group, organic particles, namely polyethylene (PE) particles, were used as macrofillers, and the relationship between the material, particle size and mixing amount of the macrofiller and the above-mentioned evaluation items was studied by changing the particle size and mixing amount. Then, except for this, the packaging material 10 for the storage device was manufactured in the same manner as in the experimental example 18-1.
[0297] The results of the above evaluation items are shown in Table 22.
[0298] [Table 22]
[0299]
[0300] (Appearance of coating film)
[0301] From this result, it can be seen that even when PE particles are used as macrofillers, when the average particle size is set to 50 μm, a substrate protection layer with a uniform and dense matte finish without a rough feeling cannot be formed. In other words, since the average particle size of the macrofiller is large, the surface of the substrate protection layer becomes matte with a rough feeling.
[0302] (PSA seal)
[0303] It can be considered that the adhesion of PSA tape will not change significantly due to the material, particle size, and mixing amount of the macrofiller.
[0304] (Protective film paste residue)
[0305] In Experimental Example 22-6, since the mixing amount of the macrofiller was too small, the adhesive of the protective film remained on the surface of the base protective layer 12. From this result, it can be considered that in order to prevent the adhesive of the protective film from remaining, even when PE particles are used as the macrofiller, the mixing amount thereof can be set to 3% by mass or more.
[0306] (Appearance after molding)
[0307] In Experimental Example 22-4, the blending amount of the large filler was 25 mass %, and since the total blending amount of the large filler and the small filler was too large, 55 mass %, gloss (glossiness) was generated on the base protective layer after cold forming.
[0308] (film thickness)
[0309] In the 1st to 21st experimental example groups, the film thickness of the substrate protective layer 12 is the same as the particle size of the large filler, but in the 22nd experimental example group using PE particles as the large filler, the film thickness of the substrate protective layer 12 is significantly smaller than the particle size of the large filler. This is because, in the lamination process when making the packaging material 10 for the storage device, the PE particles are deformed by heat. Even in this case, except for Experimental Example 22-6, the PSA adhesion and the residual protective film paste are good. In addition, except for Experimental Example 22-7, the appearance of the coating is also good. In addition, no cracks were observed in the appearance after molding in any of the experimental examples.
[0310] <Investigation Summary>
[0311] The above results can be summarized as follows.
[0312] (Appearance of coating film)
[0313] In order to obtain a substrate protective layer having a uniform and dense matte appearance without a rough feeling, the following conditions 1-1 to 1-4 may be satisfied.
[0314] Condition 1-1: The average particle size of the small filler is set to 1 to 5 μm.
[0315] Condition 1-2: The mixing amount of the small filler is set to 5% by mass or more.
[0316] Condition 1-3: The average particle size of the macrofiller is set to 30 μm or less.
[0317] Condition 1-4: The compounding amount of the macrofiller is set to 25% by mass or less.
[0318] (PSA seal)
[0319] When the PSA tape is attached to the substrate protective layer, in order to achieve strong adhesion between the two, the following conditions 2-1 to 2-3 may be satisfied. In order to achieve stronger adhesion, condition 2-4 may be satisfied.
[0320] Condition 2-1: The average particle size of the small filler is set to 1 μm or more.
[0321] Condition 2-2: The blending amount of the macrofiller is set to 1 mass % or more.
[0322] Condition 2-3: The mixing amount of the small filler is set to 5 mass % or more.
[0323] Condition 2-4: An alicyclic polyisocyanate is used as at least a part of the polyisocyanate component.
[0324] (Protective film paste residue)
[0325] In order to prevent the adhesive of the protective film from remaining on the surface of the base protective layer when the protective film is attached to the base protective layer and then peeled off, the following conditions 3-1 and 3-2 may be satisfied.
[0326] Condition 3-1: The average particle size of the macrofiller is set to 10 μm or more.
[0327] Condition 3-2: The blending amount of the macrofiller is set to 3% by mass or more.
[0328] (Appearance after molding)
[0329] In order to prevent cracks from being generated in the base protective layer when the packaging material for a power storage device is cold-formed, the following conditions 4-1 and 4-2 may be satisfied.
[0330] In addition, at this time, in order to keep the gloss in the state before cold forming, it is sufficient to satisfy the following condition 4-3 or condition 4-4.
[0331] Condition 4-1: The total amount of the large filler and the small filler mixed is 50% by mass or less.
[0332] Condition 4-2: An aliphatic polyisocyanate or an aromatic polyisocyanate is used as at least a part of the polyisocyanate component.
[0333] Condition 4-3: Inorganic particles are used as the macrofiller.
[0334] Condition 4-4: Polyethylene particles are used as the macrofiller.
[0335] Explanation of symbols
[0336] 1…battery element, 2…lead, 10…packaging material, 10a…recess, 10b…cover, 11…base material layer, 12…base material protection layer, 13…adhesive layer, 14…metal foil layer, 15a…corrosion-resistant layer, 15b…corrosion-resistant layer, 16…adhesive layer, 17…sealant layer, 20…secondary battery.
Claims
1. A packaging material for an electrical storage device, wherein: The invention comprises, in order from at least the outer surface side, a base material protection layer, a base material layer, an adhesive layer, a metal foil layer, and a sealant layer, The substrate protective layer is formed by curing a curable resin mixed with a plurality of particles having different average particle sizes. The curable resin is composed of a polyol component as a main component and a polyisocyanate component as a curing agent. Among the plurality of particles, when the particles with a larger average particle size are used as large fillers and the particles with a smaller average particle size are used as small fillers, The average particle size of the large filler is greater than 10 μm, and the average particle size of the small filler is greater than 1 μm. Furthermore, the mixing amount of the large filler accounts for 3% by mass or more of the substrate protective layer, and the mixing amount of the small filler accounts for 5% by mass or more of the substrate protective layer. The plurality of particles are organic particles such as polyolefin particles, acrylic particles, urethane particles, and polyester particles, or inorganic particles such as silicon oxide particles, aluminum oxide particles, barium sulfate particles, calcium carbonate particles, and titanium oxide particles.
2. The packaging material for a power storage device according to claim 1, wherein The average particle size of the large filler is 30 μm or less, the average particle size of the small filler is 5 μm or less, and the mixing amount of the large filler is 25% by mass or less.
3. The packaging material for a power storage device according to claim 1 or 2, wherein At least a part of the polyisocyanate component is composed of alicyclic polyisocyanate.
4. The packaging material for a power storage device according to claim 1 or 2, wherein At least a part of the polyisocyanate component is composed of aliphatic polyisocyanate or aromatic polyisocyanate. The blending amount of the large filler is 25% by mass or less, and the total blending amount of the large filler and the small filler is 50% by mass or less.
5. The packaging material for a power storage device according to claim 1 or 2, wherein The macrofiller comprises particles of organic matter.
6. The packaging material for a power storage device according to claim 5, wherein The macrofiller includes thermoplastic organic particles, and the thickness of the substrate protection layer is less than 10 μm.
7. The packaging material for a power storage device according to claim 1 or 2, wherein The macrofiller comprises inorganic particles.
8. The packaging material for a power storage device according to claim 1 or 2, wherein The adhesive layer is mixed with a coloring pigment.
Citation Information
Patent Citations
External facing material for power storage device
JP2013101765A
Packaging material for electrochemical cell
JP2014007131A
Outer packaging material for electricity storage device
JP2016195084A
Outer packaging material for power storage device, and method for manufacturing outer packaging material for power storage device
JP2017139122A